Amide and Urea Ferrocene-Containing Macrocycles Capable of the Electrochemical Sensing of Anions - Evans, N; Serpell, C; Christensen, K; Beer, P (2012)
Two novel macrocycles that incorporate the redox-active ferrocene motif have been synthesized. The amide-containing macrocycle is capable of sensing basic oxoanions such as dihydrogen phosphate and benzoate despite only exhibiting weak binding of these anions. The second macrocycle, which incorporates urea functionality, is capable of binding and sensing a greater range of anions with a maximum shift of the ferrocene/ferrocenium redox couple of -170 mV observed upon addition of an excess amount of dihydrogen phosphate. Two macrocycles that incorporate the redox-active ferrocene motif for anion sensing are presented. The urea macrocycle binds anions more strongly than the amide macrocycle and exhibits greater shifts of the ferrocene/ferrocenium redox couple upon the addition of anions. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.